(untitled) (Scientific Journal of Research Studies in Future Psychology, 2025)
The present study aimed to investigate the mediating role of mental health in the relationship between job stress and job performance among secondary school teachers in Borazjan. This research employed a descriptive–correlational design. The statistical population included all secondary school teachers in Borazjan (N = 300), of whom 169 participants (96 men and 73 women) were selected using stratified proportional random sampling based on Krejcie and Morgan’s table. Data were collected through the Job Stress Questionnaire by Hellriegel and Slocum (2000), the General Health Questionnaire (GHQ-28) by Goldberg and Hiller (1979), and Paterson’s Job Performance Questionnaire (1970). Data analyses were conducted using descriptive statistics, Pearson correlation coefficient, multiple regression, and Baron and Kenny’s mediation test with SPSS 26. The findings indicated that job stress had a significant negative relationship with both mental health and job performance, while mental health showed a significant positive relationship with job performance. Path analysis results revealed that mental health plays a mediating role in the relationship between job stress and job performance. This mediating effect was stronger among female teachers compared to male teachers. Reliability indices and model fit indices were also within acceptable ranges. In conclusion, reducing job stress and enhancing mental health can significantly improve teachers’ job performance.